Caracterização de argilas empregadas na produção de cerâmica vermelha na cidade de Santarém-Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
In the Western Region of Pará there are several industries of red ceramics that fit the national scenario where the productive process is based on empirical knowledge. However, the demand for these products, mainly for civil construction, requires more resistant and with competitive price for the ceramic products, requirements that can be reached with the scientific knowledge of the raw material which would result in optimized formulations of the ceramic masses, possible aggregations of other low-cost raw materials, with better results, and reduction of losses in the production process. The present paper deals with the characterization of clays used as raw materials for small industries producing blocks and ceramic tiles, using X-ray diffraction (XRD), infrared spectroscopy (FTIR) and Atterberg limits. In this case, the limits of liquidity and plasticity and plasticity index were evaluated. For all the samples, the XRD technique allowed to identify the main mineralogical phases and common to the clays used by the industries of red ceramics. The mineral phases identified were: quartz, kaolinite, ilite / mica, goethite, anatase, vermiculite and muscovite. The analysis through FTIR was complementary to the XRD results, and it is possible to identify absorption bands characteristic of some clay minerals identified in X-ray diffraction analyses. The results obtained by Atterberg limits, finding limits of liquidity and plasticity and plasticity index, in percentage, for all clay samples, got a reasonable satisfaction of minimum molding and extrusion requirements in the red ceramic industries.
Keywords: Argilas; Cerâmica vermelha; Caracterização mineralógica; CNPQ::CIÊNCIAS EXATAS E DA TERRA